Assessment of inter-regional dietary differences in anadromous Arctic Char (Salvelinus alpinus) in Nunavik, Canada, and links with flesh quality indicators - Sara Bolduc; Mélanie Lemire; Jean-Éric Tremblay; Marianne Falardeau; Xavier Dallaire; Mylène Brochu; Justine Legros; Jean-Sébastien Moore (Arctic Science, 2024)
Arctic Char (Salvelinus alpinus) is a salmonid fish that is the second-most consumed country food species by Nunavimmiut. Its nutritional quality is determined by omega-3 fatty acids and carotenoid pigments. Those molecules cannot be synthetized by fish and must be acquired through diet. We sampled Arctic Char in 10 rivers from three marine coastal regions of Nunavik (Hudson Bay, Hudson Strait and Ungava Bay) and described diet (stable isotopes δ13C & δ15N) and flesh quality (fatty acids and carotenoids) and assessed associations between diet and flesh quality (including also bio-impedance and colorimetry). Our results suggested inter-regional differences in the diet and nutritional quality of Arctic Char in Nunavik where δ13C values indicated that diet in Hudson Bay was more pelagic, while in Ungava Bay it was more coastal. We also observed inter-regional differences in omega-3 fatty acids and astaxanthin, the pigment responsible for the redness of the flesh color, where concentrations were highest in Ungava Bay Arctic Char. In all sampling locations, Arctic Char were an exceptional source of omega-3 fatty acids and astaxanthin, confirming its importance as a high-quality wild food. Our models suggest that astaxanthin, canthaxanthin and water content influence flesh redness. Our data highlight inter-regional differences that could be taken in consideration to better predict the impact of climate change on fish quality and, ultimately, on Inuit diet and health.